The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1017/s146239941100189x
|View full text |Cite
|
Sign up to set email alerts
|

Smith–Lemli–Opitz syndrome

Abstract: Smith-Lemli-Opitz syndrome (SLOS) is a multiple congenital malformation/intellectual disability syndrome, with clinical characteristics encompassing a wide spectrum and great variability. Elucidation of the biochemical and molecular genetic basis for the autosomal recessively inherited SLOS, specifically, understanding SLOS as a cholesterol deficiency syndrome caused by mutations in DHCR7, opened up enormous possibilities for therapeutic intervention. When cholesterol was discovered to be the activator of soni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 135 publications
(265 reference statements)
1
58
0
7
Order By: Relevance
“…Interestingly, a recent study showed that cholesterol transfer mediated by NPC2 protein is inhibited by SM excess, indicating that sphingomyelinase participates in the complex machinery that regulates the secretion of free cholesterol from the lysosomal compartment ( 19 ). Therefore, the high oxysterol levels observed In SLOS patients, the defect of 7-dehydrocholesterol reductase causes a massive accumulation of 7-dehydrocholesterol (7-DHC) ( 22 ). The fi nding of increased 7-KC alone in SLOS patients can therefore be easily explained by conversion of excessive 7-DHC into 7-KC ( 23 ).…”
Section: Patients' Resultsmentioning
confidence: 99%
“…Interestingly, a recent study showed that cholesterol transfer mediated by NPC2 protein is inhibited by SM excess, indicating that sphingomyelinase participates in the complex machinery that regulates the secretion of free cholesterol from the lysosomal compartment ( 19 ). Therefore, the high oxysterol levels observed In SLOS patients, the defect of 7-dehydrocholesterol reductase causes a massive accumulation of 7-dehydrocholesterol (7-DHC) ( 22 ). The fi nding of increased 7-KC alone in SLOS patients can therefore be easily explained by conversion of excessive 7-DHC into 7-KC ( 23 ).…”
Section: Patients' Resultsmentioning
confidence: 99%
“…anti-cortex adrenal antibodies and anti-21OH antibodies for autoimmune adrenalitis [8]) and metabolic tests (e.g. very long-chain fatty acids) for adrenoleukodystrophy or 7-dehydrocholesterol for Smith-Lemli Opitz disease [9,10], as well as markers of anticoagulation (APTT, Quick, D-dimers, anti-cardiolipin antibodies for adrenal infarction in the antiphospholipid syndrome [11]). In addition, adrenal imaging (CT or MRI) may be informative.…”
Section: Diagnosis Of Paimentioning
confidence: 99%
“…SLOS symptoms improve rapidly (though incompletely) with cholesterol supplementation and children with ASD without SLOS have been identified with low total cholesterol [65]. Total or partial deficiency of Dhcr7 causes SLOS [69]. As mentioned, several developmental disorders are associated with SLOS, including incomplete myelination, and mental retardation [70] as well as autism [64][65][66][67].…”
Section: Smith Lemli Opitz Syndromementioning
confidence: 99%